Pertumbuhan Setek Kopi Robusta (Coffea canephora P.) yang Dirangsang Dengan Urin Sapi, Air Kelapa dan Atonik dengan Berbagai Taraf Kosentrasi - I KADEK BRATA; I NYOMAN SUTEDJA; I WAYAN PASEK ARIMBAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Cuttings Growth of Robusta Coffee (Coffea canephora P.) Which is Influencedwith Urin Cow, Coconut Water and Atonic With Various Cosentration Taraf Robusta coffee (Coffea canephora P.) in general can be reproduced generatively by seeds and vegetative with cuttings, because robusta coffee pollinatesso that the development of robusta coffee is not recommended using generativemethods or with seeds because it will form new populations with varying yieldproperties. Then the multiplication of Robusta coffee is done by cuttings. This studyaims to determine the effect of the type of Growth regulator between cow urine,coconut water, and atonic and the effect of the concentration level of each type ofGrowth regulator on the growth of Robusta coffee cuttings. This study uses a nesteddesign with 3 types of zat pengatur tumbuh and 4 levels of concentration as a treatment.The results showed growth regulators Cow urine, coconut water, and atonik both canincrease the growth of Robusta coffee cuttings in nurseries depending on theconcentration given, the best growth of cuttings in the administration of cow urine witha concentration of 20% with a total oven dry weight of 2.08 g which increases cuttingsgrowth by 150.60% compared with no administration of growth regulators, Theprovision of coconut water with a concentration of 50% with a total oven dry weightreached 154 g which increased cuttings growth by 115,21% compared to withoutadministration of growth regulators. and administration of Atonik with a concentrationof 0,25% with a total oven dry weight of 141 g which increased cuttings growth by67.86% compared with no administration of growth regulators.